Effects of laser irradiation at different wavelengths (660, 810, 980, and 1064 nm) on transient receptor potential melastatin channels in an animal model of wound healing - Isman, Eren; ARAS, MUTAN HAMDİ; Cengiz, Beyhan; Bayraktar, Recep; YOLCU, ÜMİT; Topcuoglu, Tolga; Usumez, Aslihan; DEMİR, TUNCER (My University, 2015)
The aim of the present study was to compare the effectiveness of four different laser wavelengths used for low-level laser therapy(LLLT) on healing of mucositis in an animal model of wound healing, by investigating expression of transient receptor potential melastatin(TRPM) ion channels. Forty-five rats were intraperitoneally injected with 100 mg/kg 5-fluorouracil on day 1 and 65 mg/kg on day 3. Superficial scratching on left cheek pouch mucosa was performed on days 3 and 5. After ulcerative mucositis was clinically detected, LLLT was started (660 nm, HELBO; 810 nm, Fotona-XD; 980 nm, ARC-Fox; and 1064 nm, Fidelis-Plus3) at 8 J/cm(2)/day from days 1 to 4. Oval excisional biopsy was performed at the wound site, and expression of TRPM2 to TRPM8 was evaluated. Student-s t test was used for evaluation of significance of TRPM gene expression according to -0- value (alpha = 0.05). In 980-nm group, TRPM4, TRPM6, and TRPM7 were significantly higher than in the control group (p 0.05). These findings suggest that expression of TRPM6 gene was significantly affected by irradiation with lasers at different wavelengths, whereas the TRPM4 and TRPM7 genes were only expressed in the 980-nm diode laser group. TRPM6 gene was highly expressed during LLLT, which may lead to accelerated wound healing and tissue repair. In contrast, there was some evidence that the 980-nm diode laser caused increased expression of TRPM4, TRPM6, and TRPM7 which are responsible for stimulation of Ca2+ and Mg2+ metabolism, as well as apoptotic pathways of controlled cell death.